PENJADWALAN FABRIKASI PROYEK TOTALLY ENCLOSED WATER AIR COOLER (TEWAC) MENGGUNAKAN METODE PRECEDENCE DIAGRAM METHOD: STUDI KASUS PT. INTAN PRIMA KALORINDO - Ariasih, Ni Wayan Devi; Sitanggang, Bryan Estavan Imanuel; Ramdan, Hadi (LPPM Universitas Bina Bangsa, 2024)
In machine manufacturing projects, fabrication planning is an important aspect because it is the basis for fabrication activities in optimizing time. Even though planning has been carried out, delays in project completion still occur in the field. This also happened at PT Intan Prima Kalorindo. This condition is not good cause delays in project completion have several negative impacts, including; wastage of time, additional costs, physical and psychological pressure on human resources, as well as continuity of trust in the company. this research aims to create a fabrication schedule for the TEWAC procurement project using the precedence diagram method which will be presented in a gantt chart with the Microsoft project application. This research will also present a list of required material components (bill of materials), determine the sequence of operational processes followed (Operation Process Chart) as a reference in mapping relationships between work and determining activities using the Precedence Diagram Method. TEWAC's fabrication schedule after calculation analysis using the Precedence Diagram Method resulted in a shorter implementation duration than the Company's schedule. There are 19 activities that are classified as critical paths (shown in red on the Gantt chart) that need attention. This is because the critical path can cause delays in the duration of project completion. The existence of critical activities itself can be used as a reference for prioritizing work and allocating existing resources in order to minimize the level of project delays